Studying of Economic and Technical Usefulness for Projects –Proposal of New Model (Al-Mansour Journal, 2022)
This research is summarized to find out economical advantage, liable to be a guide and advisable to those who benefited of making decisions, in respect to execute or none execute of those proposed projects. The research contained two points, to study the economical advantage. First, primarily studying, is to study the probability the success of the projects or failure in general.Second, detailed study, confirming possibility the success this projects or failure. In details, lengthy and accurately from all respects. Such preparation detailed study depend on the primarily study of which it will be positively , the execution to continue , but in case shown negatively , such detailed study must not be go on, consequently in such case , if the study indication is positive, the green light lead to execute the project , the contrary is the right.Therefore according to mentioned above , the proposed typical proposal, to be helpful in order to make a decision in respect to planning projects before start to take decision that to avoid continuing works for execution , if it seems that its future results include law , and financial obligations which lead to problems and danger.